2019
DOI: 10.1111/grs.12255
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and quality of whole crop rice varieties in relation to plant components

Abstract: To expand the use of whole crop rice (WCR), accurate information on the nutritional value of newly developed varieties is required. We cultivated three new WCR varieties (Oryza sativa cv. Suweon 605, Yeongwoo and Mogwoo) developed by the National Institute of Crop Science in the southern Korean Peninsula and evaluated their feed value (crude protein, CP; acid detergent fiber, ADF; neutral detergent fiber, NDF; in vitro dry matter digestibility, IVDMD; total digestible nutrients, TDN; and relative feed value, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, the grain had no significant changes or only slightly lower fiber levels at the dough and boot stages due to the increase in nonstructural carbohydrate (e.g., starch) storage during grain development. Recently, Kim et al [8] reported that the fiber range exhibits the same trend and cannot be relied on to increase with increasing maturity. On the other hand, the crop yield increased with the stage of maturity and a similar nutritional pattern was noted in the plant heading stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the grain had no significant changes or only slightly lower fiber levels at the dough and boot stages due to the increase in nonstructural carbohydrate (e.g., starch) storage during grain development. Recently, Kim et al [8] reported that the fiber range exhibits the same trend and cannot be relied on to increase with increasing maturity. On the other hand, the crop yield increased with the stage of maturity and a similar nutritional pattern was noted in the plant heading stage.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, forage maturity analysis is an important concept used to evaluate the yield and quality of the crop. Recently, Kim et al [8] studied the forage growth stage as one of the most important factors influencing nutritional composition. However, when a plant matures, the cytoplasmic compartment levels of the cells decrease and the quantities of proteins, lipids, soluble carbohydrates, and minerals are also reduced.…”
Section: Introductionmentioning
confidence: 99%